Evaluasi Asset Management Maturity Terhadap Persyaratan Iso 55001:2014 Sebagai Dasar Penyusunan Strategi Peningkatan Manajemen Aset Pada PT PLN (Persero) UP3 Klaten : Evaluation Of Asset Management Maturity Against The Requirements Of Iso 55001:2014 As A Developing An Asset Improvement Strategy At PLN (Persero) Up3 Klaten - Fadia Afra Nazaha (Departemen Teknik Sipil ITS, 2026)
This study aims to analyze the level of asset management maturity, identify gaps, and formulate recommendations for improving the implementation of an asset management system based on ISO 55001:2014 at PT PLN (Persero) UP3 Klaten. The study employs a mixed-methods approach with a sequential explanatory design. Quantitative data were collected through a survey using the Self-Assessment Methodology Plus (SAM+) instrument, which is based on the 27 subclauses of ISO 55001:2014, while qualitative data were obtained through interviews, observations, and a review of documentation to further explore the measurement results. The results of the study indicate that the asset management maturity level of PT PLN (Persero) UP3 Klaten stands at an average score of 2.78, which falls within Level 2 (Developing). These results suggest that the organization has established asset management systems and practices in place; however, their implementation is not yet fully consistent and integrated across all aspects required by ISO 55001:2014. Of the 27 subclauses assessed, 18 were at the “Developing” level and 9 were at the “Competent” level. The subclause with the highest score was 7.2 (Competence) at 3.30, while the lowest score was for subclause 9.2 (Internal Audit) at 2.20. The results of the gap analysis identified four priority areas requiring improvement: integration of asset data, information, and communication; risk-based planning and operational controls; governance, resources, competencies, and coordination; and performance evaluation and optimization of idle assets and Non-Operational Fixed Assets (ATTB). Based on these findings, the study recommends strengthening the concept of a single source of truth (SSOT), developing a more comprehensive asset risk register, strengthening internal audits and management reviews, and formulating a strategy for optimizing idle assets and ATTB to improve the effectiveness of the asset management system’s implementation. The results of this study are expected to serve as a foundation for PT PLN (Persero) UP3 Klaten in continuously improving asset management maturity in accordance with the requirements of ISO 55001:2014.